Revisiting the sub-dialect classification of the Manggarai language in the West Manggarai Regency - Winarti, Daru; Salahuddin, Salahuddin (Research Journal in Advanced Humanities, 2024)
This study investigates sub-dialect variation of the Manggarai language spoken in the West Manggarai Regency. We surveyed ten sample survey sites and asked informants for 200 Swadesh word lists. The data was analyzed by formulating a sound correspondence system based on phonological differences between survey sites, resulting in a sub-dialect classification map. We conclude that there are three variations of the Manggarai language in West Manggarai: The Kempo sub-dialect (MSdK) which covers the districts of Komodo, Mbeliling, and Sano Nggoang; Kolang sub-dialect (MSdS>H) which is spoken in the sub-districts of Pacar, Macang Pacar, Kuwus and Kuwus Barat; This classification is proven by the sound correspondence between MSdK and MSdS>H, such as [e] – [e̯], [i] – [iə], [k] – [ʔ], [s] – [h], [c] – [s], and [h] – [ɣ]. There is also transition area sub-dialect (TAS), which classify the districts of Lembor, Lembor Selatan, Welak, Boleng, and Ndoso in the same group, showing the emergence of all linguistic features in the form of sound correspondences in the two sub-dialects with certain conditions need to be considered. This classification confirms the validity and provides evidence for the sub-dialect groupings carried out by Verheijen and refutes the Language Development and Fostering Agency, Ministry of Education and Culture, Indonesia, which is not based on scientific evidence.